Study of Leishmania pathogenesis in mice: experimental considerations. Issue 1 (December 2016) - Loeuillet, Corinne; Bañuls, Anne-Laure; Hide, Mallorie
Abstract Although leishmaniases are endemic in 98 countries, they are still considered neglected tropical diseases. Leishmaniases are characterized by the emergence of new virulent and asymptomatic strains ofLeishmania spp. and, as a consequence, by a very diverse clinical spectrum. To fight more efficiently these parasites, the mechanisms of host defense and of parasite virulence need to be thoroughly investigated. To this aim, animal models are widely used. However, the results obtained with these models are influenced by several experimental parameters, such as the mouse genetic background, parasite genotype, inoculation route/infection site, parasite dose and phlebotome saliva. In this review, we propose an update on their influence in the two main clinical forms of the disease: cutaneous and visceral leishmaniases.